The effect of a small dose of ketamine on postoperative analgesia and cytokine changes after laparoscopic cholecystectomy - Kartalov A.; Trajkov, D.; Spiroski, M.; Nikolova Todorova, Z.; Kuzmanovska B.; Dzambazovska Trajkovska, V.; Zdravkovska, M.; Karadzov, Z.; Jota, Gj.; Nojkov, J. (Macedonian Academy of Sciences and Arts, 2012)
In this study we assesed the effect of a small dose of ketamine on the production of TNFα, IL-1β and IL-6 and the postoperative pain in patients undergoing laparoscopic cholecystectomy.